Measurements of D meson decays to two pseudoscalar mesons - Mendez, H; Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Hu, D; Moziak, B; Napolitano, J; Ecklund, K; He, Q; Insler, J; et al. (2010)
Using data collected on the ψ(3770) resonance and near the Ds*±Ds" peak production energy by the CLEO-c detector, we study the decays of the possible D→PP modes and report measurements of or upper limits on all branching fractions for Cabibbo-favored, singly Cabibbo-suppressed, and doubly Cabibbo-suppressed D→PP decays except modes involving KL0 (and except D0→K+π-). We normalize with respect to the Cabibbo-favored D modes, D0→K -π+, D+→K-π +π+, and Ds+→K+KS0. © 2010 The American Physical Society.